FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PENYELESAIAN STUDI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FT-UNP - 492-501 , Elfredo Dwipa Regia (CIVED, 2015)
Abstract   This research is a qualitative descriptive research that aims to reveal the factors that influence the delay in the completion of studies students of Education Building Engineering Department of Civil Engineering FT-UNP. Allegedly there are two main factors causing delays in the student studies, which delays the completion of the course and delay the completion of the essay. Both of these factors then sought the cause in terms of both internal and external. The population in this study are students who have passed through the study of 8 semesters that of 2007, 2008 and 2009 were still active in the semester from January to June 2014. Samples were taken using the technique of "purposive proportional random sampling" with a sample size of 36 students. The instrument used was a questionnaire Likert scale models and the analysis of data using the formula percentage of degree attainment (DP). The conclusion from this study showed that the most dominant factor influence the delays in completion of the course of internal in terms of is the physical condition of the students (68.53% DP) and the external in terms of is the influence of the campus (DP 61.03%). Whereas most dominant factor influence the delays in completion of essay of internal in terms of the physical condition of students (71.76% DP) and in terms of interaction with the external is lecturers (DP 55.29%). The results of this study indicate that factors delays in completion of essay greater influence the than the study delays in completion of the course delays in factor.   Keywords: Factors, delays, study, course, essay.